2008
DOI: 10.1016/j.mseb.2007.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Ag/Na ion exchange in soda-lime glasses and the formation of small Ag nanoparticles

Abstract: We investigated the formation of very small Ag nanoparticles of 1-2 nm size in soda-lime glass with enhanced amounts of iron oxide by Ag/Na ion exchange procedures. The duration of ion exchange has been chosen between 20 and 600 h to study the processes systematically. It could be shown that structural relaxations take place as the Ag + ions were incorporated into the glass replacing the Na + of the original matrix. X-ray absorption spectroscopy at the Fe K-edge demonstrated that polyvalent Fe ions served as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 14 publications
(20 reference statements)
1
18
0
Order By: Relevance
“…224 Ag particles are detectable by absorption measurements, showing a plasmon resonance at around 400 nm. Portales et al 225 reported important results showing an enhancement of the 1?5 mm luminescence in annealed Er 3z doped Ag exchanged silicate glasses when the excitation wavelength is similar to that of the Ag plasmon absorption band.…”
Section: Waveguidesmentioning
confidence: 99%
“…224 Ag particles are detectable by absorption measurements, showing a plasmon resonance at around 400 nm. Portales et al 225 reported important results showing an enhancement of the 1?5 mm luminescence in annealed Er 3z doped Ag exchanged silicate glasses when the excitation wavelength is similar to that of the Ag plasmon absorption band.…”
Section: Waveguidesmentioning
confidence: 99%
“…The band near 766 and 426 cm À1 are due to SS mode and to a bending-rock R mode, respectively [13], as can be seen in Fig. 1.…”
Section: Resultsmentioning
confidence: 70%
“…Another band around 950 cm À1 is observed for virgin soda-lime glass as seen in curve 'a' of Fig. 1, is assigned to the SiAO À Na + stretching vibration, of NBO [13,16] and a band around 1100 cm À1 is assigned to SiAO stretching modes associated with BO. In FTIR reflectance spectra of samples after ion exchange (with and without annealing), the bands corresponding to BO ($1100 cm À1 ) and NBO ($950 cm À1 ) show detectable shifts as shown in Table 4.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Conventional experimental routes of preparation are introduction of silver ions by ion exchange followed by thermal treatment or high-energy ion implantation. There are a number of articles dealing with the preparation and structure of silver nanoparticles in silica glasses [2,3]. In cases where there is no reducing atmosphere, presence of iron oxides as an impurity (common in commercial sodalime glasses) is important for reducing silver ions, according to the reaction schema:…”
Section: Introductionmentioning
confidence: 99%